Role of microtopography in the expression of soil propagule banks on reclamation sites. (11th September 2017) - Melnik, Katharine; Landhäusser, Simon M.; Devito, Kevin
Abstract : The legacy propagule banks of salvaged topsoils are excellent sources of plant propagules for reclamation of mine sites; however, earlier studies show that less than 50% of the species found in original propagule banks actually establish. We hypothesize that the expression of this legacy propagule bank is limited by a lack of diversity of microsites and appropriate growing conditions. In an operational‐scale field experiment we manipulated topographical characteristics and substrate materials and explored early vegetation establishment on an east‐ and south‐facing slope. Three different site treatments with different microtopographic characteristics: (1) leveled surface, (2) parallel ridges, and (3) large loose piles were created using salvaged upland and lowland forest floor soil materials. Placing materials in loose hills and providing heterogeneity in substrates more than doubled plant abundance, species richness, and increased the proportion of species that require higher soil moisture. Lower micro‐elevations and northern microaspects of the microtopographic treatments had up to three times higher soil water content and double the species richness. However, the overall slope aspect had a modulating effect on microtopographic positions. The greatest treatment effect of micro‐elevation and microaspect on species richness and plant abundance occurred on the east‐facing slope, while the greatest effect of treatment on the proportion of species requiring higher soil moisture conditions was observed on the south‐facing slope. Variability in microtopography and substrate can create favorable growing conditions at an operational scale and help express a wider range of species from the legacy propagule bank.